Work-Life Balance, Take Home Pay and Workplace Environment: Which One has the Most Influence toward Employee Performance on Gen Z? - Hakim, Muhammad M. (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2024)
The business landscape is changing significantly and increasing the intensity of competition among companies around the world. Under these conditions, companies need to focus on improving the performance of their employees so that they have a better competitive advantage than their competitors. Various strategies that can be considered, for example, are through a work-life balance, take home pay, and workplace environment. This study aimed to analyze and determine the effect of work-life balance, take home pay, and workplace environment toward employee performance of Gen Z in Indonesia. The approach used was a quantitative approach, with data obtained from Gen Z who worked in private companies in Indonesia from March to July 2023. During the data collection period, a sample of 202 respondents was obtained through an online survey mechanism. The data collected was then analyzed using multiple linear regression analysis involving control variables in the form of gender and marital status, so that five different analysis models were obtained. The results of the study showed that: a) work-life balance has a positive and significant effect on employee performance; b) take home pay has a positive and significant effect on employee performance; c) workplace environment has a positive but not significant effect on employee performance; d) collectively, work-life balance, take home pay, and workplace environment have a positive and significant effect on employee performance, and; e) take home pay was proven to be the dominant variable in influencing employee performance of Gen Z in Indonesia who are chosen as the research sample.